Analysis of factors influencing prevalence and malignancy of thyroid nodules in various iodine uptake areas - Xie, HongLei; Pan, HaoWen; Qian, TingTing; Hou, Xin; Zhao, Meng; Che, WenJing; Li, WeiDong; Xu, Xian; Su, Yue; Li, Jia; Yue, ZongYu; Zhang, ZeXu; et al. (Frontiers in Endocrinology, 2024)
Background: The prevalence of thyroid nodules (TNs) has been increasing rapidly. However, little is known about the drivers of its high prevalence and tendency of malignancy. This study aimed to analyze the factors influencing the prevalence and malignancy of TNs in the adult population.Methods: A multi-stage stratified cluster random sampling was used to conduct a cross-sectional survey of the population in different iodine uptake areas in Anhui Province. The areas with deficient, adequate, and excess iodine intake were grouped according to population's urine iodine. A questionnaire, laboratory examination and ultrasound diagnosis were conducted on the participants. Nodules were diagnosed and distinguished using ultrasonography. Spearman rank correlation, random forest importance ranking, ROC curve, and unconditional binary logistic regression analyses were used to screen for risk factors. Results: A total of 1,697 participants (539 males and 1,158 females) aged 18-60 years were included, 355 of whom were diagnosed with TN. The prevalence of TNs was 20.9% and varied in different areas, with 21.9%, 25.8%, and 18.0% in the iodine deficient, adequate, and iodine excess areas, respectively. The prevalence of TNs in females was significantly higher than that in males (24.5% vs. 13.2%) and it increased with age. Female sex (OR,), old age (>41 years, OR, 2.00 [1.14, 3.50]) and smoking were risk factors for the development and deterioration of TNs.Conclusions: Patients with TNs should exercise caution when consuming goitrogens and adhere to a scientifically balanced diet. Given the high incidence of TNs in field setting, it is necessary to raise public health awareness among residents and perform regular thyroid ultrasound screening to facilitate early detection and treatment.